Portfolio optimisation for Malaysian Top 30 and Mid 70 assets using Mean-Mad model / Ahmad Bazli Khairuddin, Muhammad Mukhlis Kamarul Zaman and Mohd Azdi Maasar - Khairuddin, Ahmad Bazli; Kamarul Zaman, Muhammad Mukhlis; Maasar, Mohd Azdi (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This study explores Mean Absolute Deviation (MAD) model portfolio optimisation for the Top 30 and Mid 70 Malaysian assets, focusing on risk reduction for higher returns. Implementing MAD model, the research demonstrates its efficacy in achieving intended returns and managing risk for both asset categories. In the in-sample study, a trade-off between maximizing returns and risk management is observed, revealing a positive association between better returns and increased risk. Mid 70 assets show potential for smaller absolute deviation, indicating lower risk and making them ideal for portfolio optimisation. Backtesting results highlight favourable outcomes, but the study emphasizes the need for careful analysis as MAD may understate risk in some cases. Overall, the research significantly contributes to understanding portfolio optimization in the Malaysian market, showcasing MAD model flexibility and providing valuable insights for investors and financial specialists.